Risk Aversion and Trade Union Membership - Laszlo Goerke; Markus Pannenberg (Deutsches Institut für Wirtschaftsforschung (DIW), 2008)
In an open-shop model of trade union membership with heterogeneity in risk attitudes, a worker's relative risk aversion can affect the decision to join a trade union. Furthermore, a shift in risk attitudes can alter collective bargaining outcomes. Using German panel data (GSOEP) and three novel direct measures of individual risk aversion, we find evidence of a significantly positive relationship between risk aversion and the likelihood of union membership. Additionally, we observe a negative correlation between bargained wages in aggregate and average risk preferences of union members. Our results suggest that an overall increase in risk aversion contributes to wage moderation and promotes employment.
Keywords: J51; 330; Employment; membership; risk aversion; trade union